Won't you be my neighbor? : race, class, and residence in Los Angeles - Charles, Camille Zubrinsky, 1965- (Russell Sage Foundation, 2006)
"Using in-depth survey data from members of L.A.'s largest racial and ethnic groups. Won't You Be My Neighbor? explores why Los Angeles remains a segregated city. Charles finds that people of all backgrounds prefer both racial integration and a critical mass of same race neighbors."--Jacket